2020
DOI: 10.3390/s20082366
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Moving Load on Pavement Using Piezoelectric Sensors

Abstract: More and more researches have been carried out recently on Weigh-In-Motion (WIM) technology for solving the traffic safety problems caused by overload. In this article, we aim to study the measurement accuracy of the WIM system. Based on the electromechanical theory and elastic half-space method, we establish a theoretical model of multi-layer structure to investigate the correlation between the output voltage of the piezoelectric sensor and the applied force. In addition, we performed cyclic and moving load e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…The metrological properties of various load sensors (capacitive, piezoelectric, fiber optic, strain gauges, quartz, etc.) used in WIM systems are presented in detail in the papers [ 28 , 29 , 30 , 31 , 32 ]. In Figure 1 a, a standard deviation of measurement results obtained from an exemplary MS-WIM system equipped with 16 piezoelectric load sensors is presented.…”
Section: Resultsmentioning
confidence: 99%
“…The metrological properties of various load sensors (capacitive, piezoelectric, fiber optic, strain gauges, quartz, etc.) used in WIM systems are presented in detail in the papers [ 28 , 29 , 30 , 31 , 32 ]. In Figure 1 a, a standard deviation of measurement results obtained from an exemplary MS-WIM system equipped with 16 piezoelectric load sensors is presented.…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al [57] reported an exploratory study that suggests the potential use of conductive asphalt materials for self-sensing applications, because the different stages of damage evolution correspond to certain change patterns in their electrical resistivity. Xiang et al [58] reported the use of piezoelectric sensors to detect moving traffic loads on pavement, i.e., for weigh-in-motion application. Anti-icing pavements are often not designed for CI applications, but they can contribute to the mobility of surface transportation system during snowy weather.…”
Section: Self-sensing and Anti-icing Pavementsmentioning
confidence: 99%
“…Liu et al [2014] reported an exploratory study that suggests the potential use of conductive asphalt materials for self-sensing applications, because the different stages of damage evolution corresponded to certain change patterns in their electrical resistivity. Xiang et al [2020] reported the use of piezoelectric sensors to detect moving tra c loads on pavement, i.e., for the weigh-in-motion application.…”
Section: Ict Capabilitiesmentioning
confidence: 99%